Foraging Behavior of Honeybees (Apis Mellifera L.) and Ground Bumblebees (Bombus Terrestris L.) and its Influence on Seed Yield and Oil Quality of Oil Tree Peony Cultivar ‘Fengdan’ (Paeonia Ostii T. Hong et J. X. Zhang) - He, Chunling; Zhang, Kaiyue; Han, Dongbo; Wang, Shuaibing; Hou, Xiaogai; Zhu, Chaodong (Journal of Apicultural Science, 2020)
Oil peony ( spp.) is a new type of woody oil crop in China with a large cultivation area. Inadequate pollination is one of the main reasons for low seed yield. A pollination net room was built at an oil tree peony base, the numbers of honeybees ( L.) and ground bumblebees ( L.) were artificially increased and the foraging behaviors and daily activities of the two bees on the plants were observed. Four different pollination methods (honeybee pollination, ground bumblebee pollination, natural field pollination and pollination without insects) were applied. The visit interval, single-flower visit time, number of single-flower visits, number of flowers visited per minute and number of stigma contacts were compared. Meanwhile, the effects of honeybee and bumblebee pollination on the oil yield and quality of peony seeds were compared. There were noticeable differences in daily activity between honeybees and ground bumblebees. Significant differences in the single-flower visit time, visit interval and visit frequency were also observed; honeybee and ground bumblebee pollination increased the seed yield of oil tree peony by 78.74% and 31.88%, respectively. Therefore, both honeybees and ground bumblebees are effective pollinators of oil tree peony. These results provide a theoretical basis for further utilization of bee resources for oil tree peony pollination.